King IV municipal supplements: the impact on the municipal’s approach to governance - Chauke, Richard (Technium Social Sciences Journal, 2021)
In using King IV municipal supplement as a conceptual framework, this paper critically analyses the King IV supplement implementation and control system within the municipal sector. For the municipality to be trusted and accountable to the public, it needs to implement effective governance processes. The observance of municipal governance implementation framework poses a significant challenge for the municipalities. The prevalence of unsuccessful provision of essential services and unsuccessful audit is an indication of the failure by municipal boards that are charged with the implementation of effective governance practices. It is further indicative of the municipal board not to understanding their governance roles fully. The advent of King IV municipal supplement will give more impetus to the implementation of governance framework and effective control processes. The municipal supplement will serve as a guide to proper governance in the municipality and will push for all municipal stakeholders to be involved in the governance of the municipality. The implementation of the King IV municipal supplement will enable the municipality to fulfil the constitutional mandate and deliver on the essential services. It has also become evident that good governance in the municipality is beneficial for stakeholders as a well-governed organization inspires the confidence of the stakeholders and lowers the cost of its operations. Even though King IV is not law, the governance outcome that it can achieve are laudable. The adoption and implementation King IV code municipal supplements practices will become the criteria by which the required standard of care and appropriate standard of conduct of the council can measured.